ANALISIS PERAN GURU BK DALAM SESI KONSELING: BAGAIMANA TANGGUNG JAWAB DAN DUKUNGAN TERHADAP PESERTA DIDIK - Rahim, Abdul; Rahayu, Aydri; Reva, Gadies; Huiyyatul, Nasibah; Syifa, Salsabila (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
Guidance and Counseling Teachers have an important role in supporting students welfare through holistic responsibility and support in counseling sessions. The Guidance and Counseling Teachers responsibilities tend to be greater in terms of creating, managing and monitoring the counseling process. However, it is still often found that Guidance and Counseling Teachers do not agree with their greater responsibility in conducting counseling sessions. This study employs a quantitative descriptive methodology based on the use of instruments for data gathering. Focusing on the duties and support that guidance counselors provide to students, this study intends to demonstrate that, in fact, guidance professionals have more to do than students themselves during counseling sessions. This research was conducted as an effort to reveal and explain the responsibilities of a guidance and counseling teacher in the counseling process by trying to analyze quantitative data to provide truth based on data obtained through distributing questionnaires with 27 respondents who are high school (SMA) guidance and counseling teachers.